2018
DOI: 10.1590/0104-1428.11516
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and thermal and functional properties of biodegradable films produced using zein

Abstract: Research is being conducted in an attempt to produce biodegradable packaging to replace plastic products, thereby reducing solid waste disposal. In this work, zein films were produced from vegetable oils (macadamia, olive and buriti) and from pure oleic acid. The surface of zein-based films made using oleic acid has a good lipid distribution. The high content of oleic acid produced a film with the greatest elongation at break (8.08 ± 2.71%) due to the greater homogeneity of the protein matrix. The different oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 45 publications
(52 reference statements)
3
18
0
Order By: Relevance
“…This fact can be explained by the interactions among zein and the compounds of licorice EO after the preparation of the films, as it was also observed by the FTIR analysis. Similar results were previously obtained by other authors dealing with zein-based films [29].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This fact can be explained by the interactions among zein and the compounds of licorice EO after the preparation of the films, as it was also observed by the FTIR analysis. Similar results were previously obtained by other authors dealing with zein-based films [29].…”
Section: Resultssupporting
confidence: 92%
“…Nevertheless, elongation and elastic modulus were similar within all the films (Table 1). Finally, the mechanical properties of the zein-based films developed in this work, using glycerol as plasticizer, are very close to the ones obtained previously for zein films using oleic acid as the plasticizer agent [29,30], but improved upon than the ones obtained using other plasticizers (buriti oil, macadamia oil and olive oil) [29].…”
Section: Resultssupporting
confidence: 83%
“…Table 3 presents the onset decomposition and degradation temperatures, weight loss, and the volatile release rate at this temperature range, and Figure 2 shows curves of weight loss of composites and their derivatives. The zein polymer presented a water removal between 42 and 114 • C, followed by the evaporation of fatty acids or lightly stable amino-acids, and finally the maximum degradation of protein chains that occurred between 265 and 400 • C [41], as it is shown in Figure 3. The thermal stability of PLA was slightly decreased by the incorporation of zein coating due probably to the earlier degradation of this protein when compared to PLA.…”
Section: Thermogravimetric Analysismentioning
confidence: 84%
“…Almeida et al. (2018) reported that the more oleic acid content in the film matrix would be more homogeneity of the material. The oil used in this study had high oleic acid or high lauric acid content, but it still had various types of fatty acid components.…”
Section: Resultsmentioning
confidence: 99%
“…Almeida et al. (2018) reported that the zein‐based films made using oleic acid had a good lipid distribution in the matrix, improved the thermal, and enhanced mechanical properties of the films. Moreover, the addition of vegetable oils such as rapeseed oil, coconut oil, or hazelnut oil in the mixture of sodium alginate and apple puree film was reported to visually attractive, flexible, thermodynamically compatible edible films (Kadzińska, Bryś, Ostrowska‐Ligęza, Estéve, & Janowicz, 2020).…”
Section: Introductionmentioning
confidence: 99%